Efficacy and safety of galcanezumab for the prevention of episodic migraine: Results of the EVOLVE-2 Phase 3 randomized controlled clinical trial - Skljarevski, Vladimir; Matharu, Manjit; Millen, Brian A; Ossipov, Michael H; Kim, Byung-Kun; Yang, Jyun Yan (Cephalalgia, 2018)
Introduction Galcanezumab is a humanized monoclonal antibody binding calcitonin gene-related peptide, used for migraine prevention. Methods A global, double-blind, 6-month study of patients with episodic migraine was undertaken with 915 intent-to-treat patients randomized to monthly galcanezumab 120 mg (n = 231) or 240 mg (n = 223) or placebo (n = 461) subcutaneous injections. Primary endpoint was overall mean change from baseline in monthly migraine headache days. Key secondary endpoints were ≥50%,  ≥ 75%, and 100% response rates; monthly migraine headache days with acute migraine medication use; Patient Global Impression of Severity rating; the Role Function-Restrictive score of the Migraine-Specific Quality of Life Questionnaire. Results Mean monthly migraine headache days were reduced by 4.3 and 4.2 days by galcanezumab 120 and 240 mg, respectively, and 2.3 days by placebo. The group differences (95% CIs) versus placebo were 2.0 (−2.6, −1.5) and 1.9 (−2.4, −1.4), respectively. Both doses were superior to placebo for all key secondary endpoints. Injection site pain was the most common treatment-emergent adverse event, reported at similar rates in all treatment groups. Both galcanezumab doses had significantly more injection site reactions and injection site pruritus, and the 240 mg group had significantly more injection site erythema versus placebo. Conclusions Galcanezumab 120 or 240 mg given once monthly was efficacious, safe, and well tolerated. Study identification EVOLVE-2; NCT02614196; https://clinicaltrials.gov/ct2/show/NCT02614196. Trial Registration NCT02614196.